Unstimulated inflammatory activity is associated with treatment response to cognitive-behavioral therapy for urologic chronic pelvic pain - McKernan, L. C.; Crofford, L. J.; Bruehl, S.; McGonigle, T. W.; Kelly, A. G.; Ryden, A. M.; Sutherland, S. L.; Clauw, D. J.; Williams, D. A.; Dmochowski, R. R.; Schrepf, A. D. (Frontiers in Pain Research, 2025)
IntroductionInterstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating urologic chronic pelvic pain condition characterized by pelvic pain and urinary symptoms. Evidence suggests that in chronic pain conditions such as IC/BPS, inflammatory markers are associated with heightened symptom severity and widespread pain. Non-pharmacological treatments such as cognitive-behavioral therapy are recommended as a core component of IC/BPS treatment. There is limited and mixed evidence as to whether inflammatory markers are affected by non-pharmacological treatments or their relationship to treatment response. This exploratory study considered how inflammatory characteristics may both predict and explain treatment response in a sample of females with interstitial cystitis.MethodParticipants were randomized to receive either 8-weeks of telemedicine-delivered cognitive-behavioral therapy (CBT) or an active attention control. Six cytokine/chemokines in whole blood plasma (IL-6, IL-8, IL-10, IL-1β, and TNF-α) were assessed in a subset of trial participants at baseline, post-treatment, and at five months. We assessed relationships between baseline plasma inflammatory cytokine levels and self-reported symptoms, changes in cytokines over time, and how baseline cytokine levels may relate to clinically meaningful indicators of change following CBT.ResultsCytokine/chemokine levels did not significantly change over time. Higher levels of unstimulated IL-1β were associated with significantly worse clinical pain characteristics and greater degree of CBT treatment response.DiscussionThis suggests that individuals with greater degrees of inflammation may derive more benefit from the self-regulation training, pain coping strategies, and cognitive reframing offered in CBT for pain.